2019
DOI: 10.1029/2018ja026365
|View full text |Cite
|
Sign up to set email alerts
|

Solar Rotation Period Driven Modulations of Plasmaspheric Density and Convective Electric Field in the Inner Magnetosphere

Abstract: This paper presents the first analysis of Van Allen Probes measurements of the cold plasma density and electric field in the inner magnetosphere to show that intervals of strong modulation at the solar rotation period occur in the locations of the outer plasmasphere and plasmapause (~0.7 R E peak-to-peak), in the large-scale electric field (~0.24 mV/m peak-to-peak), and in the cold plasma density (~250 to~70 cm −3 peak-to-peak). Solar rotation modulation of the inner magnetosphere is more apparent in the decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In addition to the wave environment, we seek to understand the local plasma conditions (e.g., Thaller et al, ; Hwang & Yoon, , in this collection) that lead to the enhancement or suppression of these various wave modes and the consequences therein for the precipitation of the trapped populations. For instance, Greeley et al () in this collection have found that the plasmapause is likely a better indicator of microburst location than L‐shell.…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…In addition to the wave environment, we seek to understand the local plasma conditions (e.g., Thaller et al, ; Hwang & Yoon, , in this collection) that lead to the enhancement or suppression of these various wave modes and the consequences therein for the precipitation of the trapped populations. For instance, Greeley et al () in this collection have found that the plasmapause is likely a better indicator of microburst location than L‐shell.…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…An alternative to this L pp definition is to use a density threshold (n e ) of 100 cm −3 to infer the plasmapause. Many studies have utilized the density threshold as a proxy of the plasmapause position (Chappell et al, 1970;Malaspina et al, 2016;Thaller et al, 2019). In Thaller et al (2019), they derived the plasmapause using both the plasma density gradient and density threshold methods and demonstrated that these two quantities are comparable.…”
Section: Plasmapause: Definition Determination and Simulationsmentioning
confidence: 99%
“…Many studies have utilized the density threshold as a proxy of the plasmapause position (Chappell et al, 1970;Malaspina et al, 2016;Thaller et al, 2019). In Thaller et al (2019), they derived the plasmapause using both the plasma density gradient and density threshold methods and demonstrated that these two quantities are comparable. They further noted that the plasmapause derived from the density threshold has fewer gaps, thanks to its simplicity of implementation.…”
Section: Plasmapause: Definition Determination and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations